A dithieno[3, 2-b:2′, 3′-d]pyrrole-cored four-arm hole transporting material for over 19% efficiency dopant-free perovskite solar cells. Issue 31 (25th July 2019) - Dong, Zihao; Yin, Xinxing; Ali, Amjad; Zhou, Jie; Bista, Sandip Singh; Chen, Cong; Yan, Yanfa; Tang, Weihua
Abstract : A dithieno[3, 2- b :2′, 3′- d ]pyrrole-cored four-arm hole transporting material has been designed to realize over 19% efficiency dopant-free perovskite solar cells. Abstract : Dopant-free hole transporting materials (HTMs) have been in the limelight in the quest for stable perovskite solar cells (PVSCs). Herein, we report a novel dopant-free HTM featuring a dithieno[3, 2- b :2′, 3′- d ]pyrrole core flanked with two-fold triphenylamine arm substituted thiophene bridges. This star-shaped molecule shows a suitable ionization potential (5.13 eV), good thermal stability (high glass-transition temperature of 120.3 °C) and a high hole mobility (6.50 × 10 −5 cm 2 V −1 s −1 ). The molecule is more hydrophobic than reference spiro-OMeTAD in a film. By capping our dopant-free HTM on the perovskite layer, the fabricated n-i-p device can achieve a maximum power conversion efficiency of 19.42%, which is comparable to the device based on doped spiro-OMeTAD (19.59%). This star-shaped dithieno[3, 2- b :2′, 3′- d ]pyrrole based molecule is thus a promising candidate HTM for upscaling the commercial manufacture of PVSCs.